Applicability of the SNPforID 52-plex panel for human identification and ancestry evaluation in a Brazilian population sample by next-generation sequencing. (May 2019) - Valle-Silva, Guilherme do; Souza, Flávia Djenane Nunes de; Marcorin, Letícia; Pereira, Alison Luis Eburneo; Carratto, Thássia Mayra Telles; Debortoli, Guilherme; Oliveira, Maria Luiza Guimarães de; Fracasso, Nádia Carolina de Aguiar; Andrade, Edilene Santos de; Donadi, Eduardo Antônio; Norton, Heather L.; Parra, Esteban J.; et al.
Highlights: The SNP for ID 52-plex system was analyzed in a Brazilian population sample ( n  = 340). Next-generation sequencing was performed with the HaloPlex and MiSeq approaches. On average, 50.5 genotypes were called in each sample. Combined match probability of 6.48 × 10 −21 and exclusion power of 0.9997 were found. Admixture tools revealed predominant European contribution and low Amerindian input. Abstract: SNP analysis is of paramount importance in forensic genetics. The development of new technologies in next-generation sequencing allowed processing a large number of markers in various samples simultaneously. Although SNPs are less informative than STRs, they present lower mutation rates and perform better when using degraded samples. Some SNP systems were developed for forensic usage, such as the SNP for ID 52-plex, from the SNP for ID Consortium, containing 52 bi-allelic SNPs for human identification. In this paper we evaluated the informativeness of this system in a Brazilian population sample ( n = 340). DNA libraries were prepared using a customized HaloPlex Target Enrichment System kit (Agilent Technologies, Inc.) and sequenced in the MiSeq Personal Sequencer platform (Illumina Inc.). The methodology presented here allowed the analysis of 51 out of 52 SNP for ID markers. Allele frequencies and forensic parameters were estimated, revealing high informativeness: the combined match probability and power of exclusion were 6.48 × 10 −21 and 0.9997, respectively. Population admixture analysis indicates high European contribution (more than 70%) and low Amerindian contribution (less than 10%) in our population, while individual admixture analyses were consistent with the majority of individuals presenting high European contribution. This study demonstrates that the 52-plex kit is suitable for forensic cases in a Brazilian population, presenting results comparable with those obtained using a 16 STR panel.